In the shadow of blackbirds a novel - Winters, Cat. (Amulet Books, 2013)
In San Diego in 1918, as deadly influenza and World War I take their toll, sixteen-year-old Mary Shelley Black watches desperate mourners flock to séances and spirit photographers for comfort and, despite her scientific leanings, must consider if ghosts are real when her first love, killed in battle, returns.